2019
DOI: 10.1088/1538-3873/ab1a46
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Method for a Photon-counting Laser Coherence Detection System to Complement Optical SETI

Abstract: The detection of laser radiation originating from space is a positive indicator of Extra Terrestrial Intelligence (ETI). Thus far the optical search for ETI (OSETI) has looked for enhanced brightness in the form of either narrow-band spectral emission or time correlated photons from laser pulses. In this paper it is proposed to look for coherence properties of incoming light in a manner that can distinguish against atomic emission lines. The use of photon sensitive detectors and a modulating asymmetric interfe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…As with conventional laser detection the approaches taken have been on observing the relative brightness -either in high resolution spectroscopy [23], or in short pulse coincidence detection [24]. Benton [25] has recently shown that coherence detection can be applied to this problem at the level of single photon detection and can offer potential improvements in sensitivity to around 1 photon/m 2 /s and detection of both CW and pulsed lasers.…”
Section: Discussionmentioning
confidence: 99%
“…As with conventional laser detection the approaches taken have been on observing the relative brightness -either in high resolution spectroscopy [23], or in short pulse coincidence detection [24]. Benton [25] has recently shown that coherence detection can be applied to this problem at the level of single photon detection and can offer potential improvements in sensitivity to around 1 photon/m 2 /s and detection of both CW and pulsed lasers.…”
Section: Discussionmentioning
confidence: 99%
“…), it was already suggested by Kingsley (1993) to employ heterodyne and homodyne detection. A recent proposal by Benton (2019) proposes a method for a photon-counting laser coherence detection system. Based on an asymmetric Mach-Zehnder interferometer, it is equally sensitive to pulsed and continuous signals.…”
Section: Laser Warners and Phase Coherencementioning
confidence: 99%
“…Finally, coherence detecting systems of various types, like laser warners, should be pointed towards the stars. One example is the asymmetric Mach-Zehnder interferometer described by Benton (2019).…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%